Effect of supplementation of newborn piglets with spray dry blood plasma on weight gain and serum biochemical variables - Schuh S.* (2016)
© 2016, Springer-Verlag London.The aim of this study was to evaluate the effect of ​spray dry blood plasma (SDBP) supplementation for newborn piglets on performance, seric biochemical variables, total antioxidant levels, and nitric oxide. Thus, 20 newborn piglets, with lower body wheith (1.179 ± 0.276 kg) were distributed in an experimental design with five randomized blocks (females were considered block), with two treatments and ten repetitions. The treatment consisted to provide 10 g of SDBP (group T), previously diluted at 1:4 (blood plasma/water) administered for the first hour post-birth of the piglets, and a control group (group C; without blood plasma administration). The performance of newborn piglets was evaluated at days 1, 8, 15, 22, and 28 after birth, and the seric biochemical variables (cholesterol, triglycerides, gamma-glutamyl transferase (GGT), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and urea), total antioxidant levels by ferric reducing ability of plasma (FRAP) method, and nitrite/nitrate (NOx) levels were evaluated at days 5, 15, and 22 post-birth of the piglets. No difference was observed in treatments (groups C and T) for weight gain, as well as for the most biochemical variables, except GGT and NOx (P < 0.05). There was a significant effect (P < 0.05) on age for ALT, AST, and FRAP, i.e., these variables increase in serum. Triglyceride levels have a tendency for reduction (P = 0.07) according to the age. GGT activity and NOx levels were lower (P < 0.05) in group T, as well as the AST levels that showed a tendency for reduction in this group compared to group C. Therefore, supplementation with 10 g for SDBP did not interfere in the weight gain, but altered the GGT activity and NOx levels in the serum of newborn piglets with low weight.